Phytochemical Profile and Antioxidant Activity of Extracts of the Peruvian Peppertree Schinus Areira L. from Chile - Martinez-Salinas, J; Rios-Ramirez, M (Elsevier B.V., 2021)
The Andean tree Schinus areira L. has multiple traditional uses, from the treatment of bronchitis and rheumatic diseases to menstrual cycle regulation and wound healing. With reported hypotensive, analgesic, antitumoral and anti-inflammatory properties, it acts predominantly against diseases related to oxidative stress. This study focuses on the antioxidant activity and phytochemical profile of the extracts of Schinus areira L. Serial extraction of the fruits was performed both by maceration and by Soxhlet. Total phenols and flavonoids were measured using the Folin-Ciocalteu method and AlCl3, respectively. In vitro antioxidant activity was determined by FRAP and DPPH. Results were similar for both extraction methods. Primary metabolites detected included carbohydrates, proteins and amino acids; secondary metabolites included tannins, flavonoids, saponins, steroids and triterpenes. Antioxidant activity was confirmed for ethyl acetate, methanolic and aqueous extracts. The methanolic extract had both the highest polyphenol content (>195 mg GAE/ g dry weight) and the highest antioxidant activity [EC50 > 476 μg/mL; >273 mg AA/g dry weight (DPPH); >301 mg AA/ g dry weight (FRAP)]. The extract does not produce macrophage cytotoxicity in RAW 264.7, which is indicated by an average cytotoxicity of 2% over 24 h. Our study serves as a starting point for future research on the pharmacological properties of Schinus areira L. © 2020 The Authors